The Essential Role Played by B Cells in Supporting Protective Immunity Against Trichuris muris Infection Is by Controlling the Th1/Th2 Balance in the Mesenteric Lymph Nodes and Depends on Host Genetic Background - Sahputra, Rinal; Ruckerl, Dominik; Couper, Kevin N.; Muller, Werner; Else, Kathryn J. (Frontiers in Immunology, 2019)
How B cells contribute to protective immunity against parasitic nematodes remains unclear, with their importance as accessory cells under-explored. By using anti-CD20 monoclonal antibody (mAb) (Genentech-clone 5D2) to deplete B cells in two genetically distinct strains of mouse, C57BL/6 and BALB/c, this study reveals that, on the C57BL/6 genetic background, B cells are important for the expulsion of Trichuris muris (T. muris) by acting as accessory cells, supporting Th2 immune responses. C57BL/6 mice receiving anti-CD20 treatment prior to and during T. muris infection, or anti-CD20 treatment that commenced two weeks post infection (p.i.), were susceptible to high dose T. muris infection. In complete contrast, BALB/c mice were still able to expel T. muris in the absence of B cells. Th2 type cytokines produced by mesenteric lymph nodes (MLN) cells from C57BL/6 mice receiving α-CD20 mAb treatment were significantly lower than produced by cells from isotype control treated mice. Interestingly, although the production of IFN-γ in the MLN of C57BL/6 mice receiving α-CD20 mAb treatment was not affected, the expression of IFN-γ and IFN-γ induced genes at the effector site, the gut, were significantly increased compared to isotype control treated mice, reflecting the overall change in Th1/Th2 balance in favour of Th1. To explore whether the important role played by the B cell in the protective immune response of C57BL/6 mice was in enabling strong Th2 responses in the context of mixed Th1/Th2 settings, IFN-γ was blocked using anti-IFN-γ mAb post B cell depletion. Neutralization of IFN-γ restored the resistance against T. muris infection in the absence of B cells. Thus, our data suggest an important role of B cells in supporting Th2 type immune responses in mixed IFN-γ-rich Th1/Th2 settings.